2017
DOI: 10.1021/acscatal.7b02248
|View full text |Cite
|
Sign up to set email alerts
|

Cp*CoIII-Catalyzed Branch-Selective Hydroarylation of Alkynes via C–H Activation: Efficient Access to α-gem-Vinylindoles

Abstract: An efficient, atom-economical, and regioselective insertion of indoles into terminal alkynes has been realized via cobalt­(III)-catalyzed C–H activation under mild conditions, leading to efficient synthesis of α-gem-vinylindoles. The insertion of the alkynes follows a rare 1,2-selectivity, and silyl alkynes, alkyl alkynes, propargyl alcohols, and protected propargyl amines are all applicable. The mechanism of this hydroarylation system has been studied in detail by a combination of experimental and computation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(40 citation statements)
references
References 113 publications
(32 reference statements)
1
39
0
Order By: Relevance
“…On the basis of these control experiments and previous reports,[2g], [7a], [7d], , the plausible catalytic cycle is shown in Scheme . The active cationic species I is generated in the presence of Cp*Co(CO)I 2 , AgSbF 6 , and pivOH, which then undergoes electrophilic metalation with 1a in a reversible manner to form cobaltacycle II upon the release of pivOH.…”
Section: Methodssupporting
confidence: 54%
See 1 more Smart Citation
“…On the basis of these control experiments and previous reports,[2g], [7a], [7d], , the plausible catalytic cycle is shown in Scheme . The active cationic species I is generated in the presence of Cp*Co(CO)I 2 , AgSbF 6 , and pivOH, which then undergoes electrophilic metalation with 1a in a reversible manner to form cobaltacycle II upon the release of pivOH.…”
Section: Methodssupporting
confidence: 54%
“…While the desired product was not detected without an acidic additive (entries 1–3), product 3aa was obtained in a 16 % yield with AcOH (2 equiv.) (entry 4), The C(sp 2 )–H alkenylation product 4aa (11 % yield), which is synthesized through the β‐hydride elimination after migratory insertion into alkenes, was also isolated. In the presence of the AgSbF 6 additive, other acids were screened (entries 5–7), and pivOH (pivalic acid) was identified to be the most powerful for linear‐selective C–H alkylation (entry 5).…”
Section: Methodsmentioning
confidence: 99%
“…This protocol has significantly broadened the scope of the indole C‐2 alkenylation. Inspired by this report, Li group has demonstrated the regioselective insertion of indoles into terminal alkynes using a Co(III) catalyst . The addition of alkynes followed a rare 1,2‐selectivity leading to α‐gem‐ vinylindoles.…”
Section: Alkenylation Reactionsmentioning
confidence: 98%
“…Inspired by this report, Li group has demonstrated the regioselective insertion of indoles into terminal alkynes using a Co(III) catalyst. [38] The addition of alkynes followed a rare 1,2-selectivity leading to α-gem-vinylindoles. This method applies to silyl alkynes, alkyl alkynes, propargyl alcohols and protected amines.A comprehensive mechanistic study by the authors suggests that the steric or electronics on the alkynes are responsible for the observed selectivity depending upon the substrates.…”
Section: Co-catalyzed Reactionsmentioning
confidence: 99%
“…An uncommon regioselective 1,2‐insertion reaction of indole with wide range of alkyne was achieved by Li/Lan and co‐workers in the presence of Cp*Co(III)‐catalyst (Scheme ). A series of experimental and theoretical investigations were performed to understand insight the mechanism of the reaction.…”
Section: Construction Of C−c Bondmentioning
confidence: 99%